SEXUAL EDUCATION MAPS GAME FROM LOCAL TO DIGITAL: STRENGTHENING CHILDREN’S CAPACITY TO PREVENT SEXUAL VIOLENCE - Ubudiyah, Masunatul; Angel, Syalaisyah; Nur, Sarah; Bunga, Erlistya; Meylinda, Elsa; Nabilah Dzawinnuha, Salma (Universitas Airlangga, 2025)
Introduction: Sexual violence against children remains a serious issue in Indonesia, with increasing cases each year due to limited sexual literacy and awareness among children. This community service program aimed to enhance children’s knowledge and self –awareness in preventing sexual violence through innovative educational approach using the Sexual Education Maps Games (SEMAPS) based on a local-to-digital model. Methods: This program was implemented using a participatory and educational approach at a community-based educational institution involving 32 children aged 6-12 years and 6 educators. The intervention combined empowerment, training, and technological mentoring using SEMAPS as a game-based learning tool. Data were collected through pre-and post-tests using structured questionnaires to measure children’s knowledge. Statistical analysis was conducted using paired sample t-test with a significance level of p<0.05. Results: A significant improvement in children’s understanding after the intervention. The average pre-test score was 7.38 (SD= 1.755) and increased to 8.81 (SD = 0.535) in the post-test,, with a mean difference of 1.43 points (p = 0.000). The result indicate that the use of interactive game-based education effectively inched children’s awareness and comprehension of safe touch, unsafe touch, and appropriate reporting behavior. Additionally, empowerment can lead the teacher’s capacity to deliver sexual education. Conclusion: By integrating cultural values and digital learning technology, this innovation supports the achievement of Sustainable Development Goals (SDGs) number 2 and 5, promoting inclusive, safe, and quality education. The SEMAPS model can serve as a replicable framework for other institutions to develop interactive, culturally relevant, and sustainable sexual education programs.